PSYCHOSOCIAL RECOVERY EFFORTS FOR CHILDREN AFFECTED BY SOCIAL CONFLICT IN MASIHULAN VILLAGE - Nurlaila Sopamena; Janaba Renngiwur; Nur Tunny; Andi Masniati; Radhika Fardha Lestaluhu; Samlan Rumain; Sucitra Jija'a; Muhammad Fadhil Basta; Mita Amelia (Suluh Adiluhung Publisher (SAPub), 2025)
The social conflict that occurred in Negeri Masihulan, Central Maluku Regency, following Eid al-Fitr 2025 has left serious psychosocial impacts, particularly on children. The trauma experienced by child victims of the conflict has the potential to disrupt their emotional, social, and cognitive development if not promptly addressed. Trauma healing activities have become an essential effort in providing psychosocial support to children, helping them recover from their traumatic experiences. This article aims to describe the implementation of a trauma healing program as both a psychosocial education medium and a form of legal protection for children affected by social conflict in Negeri Masihulan. The program was carried out by lecturers and students of IAIN Ambon in collaboration with the local community. The implementation methods included icebreaking sessions, educational games, group singing, and the delivery of peace messages by traditional leaders and village authorities. The results of the activity indicated positive behavioral changes among the children, who initially displayed signs of anxiety and withdrawal but later became more cheerful, active, and willing to engage in social interactions. In addition to contributing to the psychological recovery of the children, the program also succeeded in fostering a peaceful atmosphere within the community through a local wisdom-based approach. This trauma healing initiative functions not only as a form of social rehabilitation for child victims of conflict but also as part of a learning process to instill social values and peace education integrated with local traditions. The findings suggest that community-based trauma healing programs can serve as effective instruments for social education and conflict resolution, particularly in conflict-prone areas.